Conspiratorial Beliefs About COVID-19 Pandemic - Can They Pose a Mental Health Risk? The Relationship Between Conspiracy Thinking and the Symptoms of Anxiety and Depression Among Adult Poles - Dȩbski, Paweł; Boroń, Adrianna; Kapuśniak, Natalia; Dȩbska-Janus, Małgorzata; Piegza, Magdalena; Gorczyca, Piotr (Frontiers in Psychiatry, 2022)
The aim of the study was to describe the relationship between the tendency to believe in false information about the COVID-19 pandemic, tendency to believe in conspiracy theories and the severity of anxiety and depression symptoms among the surveyed Poles. The study was conducted via the Internet in a group of 700 people aged 24.7 ± 6.34 years (585 women and 110 men), using scales such as Generic Conspiracist Beliefs Scale (GCBS), Hospital Anxiety and Depression Scale (HADS) and the original questionnaire COVID-19 Conspiratorial Beliefs Scale (COVID-19 CBS) designed to measure the tendency to believe in false information about COVID-19 pandemic. A positive correlation was observed between the tendency to believe in false information about the COVID-19 pandemic (COVID-19 CBS) and the tendency to believe in general conspiracy theories (GCBS), moreover, both COVID-19 CBS and GCBS significantly positively correlated with the severity of anxiety and depression symptoms in the study group. Regression analysis showed that the increased tendency to believe in false beliefs about the COVID-19 pandemic may be associated with an increase in the severity of anxiety and depression symptoms. It can be hypothesized that the tendency to believe in false information regarding the COVID-19 pandemic is positively associated with the tendency to general belief in conspiracy theories. False beliefs about the COVID-19 pandemic may, at least to some extent, influence the development of anxiety and depression symptoms.